Bioavailability and Metabolism of Potassium Phosphanilate in Laboratory Animals and Humans - Lee, Francis H. (1980)
Phosphanilic acid is an antibacterial agent with a mode of action and antibacterial spectrum similar to those of sulfamethoxazole, with the exception that it has potent antipseudomonal activity. Bioavailability studies in rats (50, 300, and 600 mg/kg, oral and subcutaneous), dogs (50, 150, and 450 mg/kg, oral and intravenous infusion), and humans (400 and 800 mg, oral) showed that the extent of oral absorption of potassium phosphanilate was low. The bioavailability, calculated by comparing the oral values for area under the plasma concentration curve with those for the respective parenteral doses, was 10% for rats and 45 (50 and 150 mg/kg) and 19% (450 mg/kg) for dogs. The 24-h urinary recovery also confirmed the low oral bioavailability, i.e., rat, 13 (oral) and 75% (subcutaneous); dog, 15 to 29 (oral) and 87% (intravenous) of the dose. Plasma levels and urinary recovery (4%, oral) were low and variable in humans. The poor absorption of oral doses may be due to drug precipitation in the stomach, low permeability of the soluble species due to extensive in situ ionization (pK(a), 1.8 to 2) in the intestine, or first-pass metabolism to N-acetylphosphanilic acid. The plasma t(½) values after parenteral administration were 0.3 h in rats and 1.3 h in dogs. Although the lack of adequate blood levels of phosphanilic acid after oral administration in humans precludes the use of this compound for treatment of systemic infections, the sustained urinary concentration at levels severalfold higher than the minimal inhibitory concentration (1 μg/ml) for at least 10 h postdose was indicative of the therapeutic usefulness in urinary tract infections.